International lis pendens and preliminary measures [some reflections in light of the ECJ Judgments in the hanseyachts and schlömp cases] - Gascón Inchausti, Fernando (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The application of the provisions on international lis pendens established in the European regulations on civil procedure is based, ordinarily, on the prevalence of the proceeding initiated in the first place. The present work addresses, in light of two recent decisions of the Court of Justice of the European Union (in the HanseYachts and Schlömp cases) to what extent it can be understood that lis pendens, for these purposes, is produced by certain preliminary measures, prior to legal proceedings, especially when making use of them is mandatory from a legal point of view (as it can happen with a previous conciliation) or it may be necessary from a strategic point of view (this may be the case of measures to preserve or establish evidence of facts, as well as protective measures).
Keywords: Brussels I Regulation (recast); International lis pendens; Commencement of proceedings; Preliminary measures; Measures to preserve or establish evidence of facts; Conciliation